Penerapan Aspek-Aspek Ergonomi Pada Workshop Pengelasan Di LPKA Kelas II Tomohon - I Wayan Gede Suarjana; Moh Fikri Pomalingo; Bastian Rikardo Parhusip; Muh Muhdi Attaufiq (Malahayati Nursing Journal, 2022)
ABSTRACT: IDENTIFICATION OF ERGONOMIC ASPECTS AT WELDING WORKSHOP AT LPKA KELAS II TOMOHON Introduction: LPKA Kelas II Tomohon Is a Special Children's Development Institution that has the duties and functions of to build, guide and protect every student who has problems with the law. One of the coaching programs implemented is welding process training to improve the creativity of community students. Purpose: This research aims to identify the application of eight aspects of ergonomics to welding workshop participants in LPKA Kelas II Tomohon.Method: The design of this study is an observational analytical approach that is observation without intervention to uncover the facts of a cause and effect described descriptively. This research was conducted by observing the workings and work environments including, human interaction of machines, and the physical environment. This research is focused on the training process of welding practice. Respondents from this study amounted to 14 respondents who took welding training. The study was conducted from May 2021 to June 2021.Result: Based on observations and measurements that are known that in working conditions in welding workshops are still not ergonomic, it can be seen from the absence of physiological work attitude arrangements when doing activities, irregular rest arrangements, lack of muscle stretching activity at rest, and the use of welding glasses and masks that have not been applied when doing the welding process. Conclusion: Based on the identification of the application of 8 aspects of ergonomics that are still a priority of attention that are at risk of health problems in worksop participants, namely from aspects of work attitudes that are still not in accordance with physiological / ergonomic attitudes, the social condition of the participant's work culture is still lacking in the culture of the use of personal protective equipment to ensure work safety, and human-machine interaction is still not appropriate, namely from the correct use of tools in accordance with their function,  Work facilities such as desks have not met, fiber working conditions that can still pose health risks to workers that need to be a concern. Keywords: ergonomic aspects, occupational health, welding    INTISARI : IDENTIFIKASI ASPEK-ASPEK ERGONOMI DI WORKSHOP PENGELASAN DI LPKA KELAS II TOMOHON Pendahuluan: LPKA Kelas II Tomohon adalah Lembaga Pembinaan Khusus Anak yang memiliki tugas dan fungsi utnuk mebina, membimbing dan mengayomi setiap anak didik permasyarakatan yang bermasalah dengan hukum. Salah satu program pembinaan yang dilaksanakan yaitu pelatihan proses pengelasan untuk meningkatkan kreatifitas anak didik permasyarakatan.Tujuan: Penelitian ini bertujuan untuk mengidentifikasi penerapan delapan aspek ergonomi pada peserta workshop pengelasan di LPKA Kelas II Tomohon.Metode: Rancangan pada penelitian ini adalah dengan pendekatan analitik-observasional yaitu pengamatan tanpa intervensi untuk mengungkap fakta suatu sebab-akibat yang diuraikan secara deskriptif. Penelitian ini dilakukan dengan melakukan observasi terhadap cara kerja dan lingkungan kerja meliputi, interaksi manusia mesin, dan lingkungan fisik.Hasil: Berdasarkan Pengamatan dan Pengukuran yang dilakaukan diketahui bahwa pada program pengelasan dilihat dari penerapan aspek-aspek ergonomi yaitu Status gizi, sikap kerja, penggunaan tenaga otot, kondisi lingkungan, kondisi waktu, kondisi sosial, kondisi informasi dan kondisi interaksi manusia-mesin telah diterapkan walaupun dibeberapa aspek yang masih perlu diterapkan untuk terciptanya kondisi kerja yang aman, nyaman, sehat, efisen dan efektif.Simpulan: Berdasarkan identifikasi penerapan 8 aspek ergonomi yang masih menjadi prioritas perhatian yang berisiko terjadinya gangguan kesehatan pada peserta worksop yaitu dari aspek sikap kerja yang masih belum sesuai dengan sikap fisiologis/ergonomis, kondisi social budaya kerja peserta masih kurang dalam budaya penggunaan alat pelindung diri untuk menjamin keselamatan kerja, serta interaksi manusia-mesin masih belum sesuai yaitu dari penggunaan alat yang benar sesuai dengan fungsinya, fasilitas kerja seperti meja kerja belum memenuhi, serat kondisi kerja yang masih dapat menimbulkan risiko kesehatan pekerja yang perlu menjadi perhatian. Kata Kunci : aspek ergonomi, kesehatan kerja, pengelasan